2022
DOI: 10.1186/s13007-022-00840-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteome evaluation of homolog abundance patterns in Arachis hypogaea cv. Tifrunner

Abstract: Background Cultivated peanut (Arachis hypogaea, AABB genome), an allotetraploid from a cross between A. duranensis (AA genome) and A. ipaensis (BB genome), is an important oil and protein crop with released genome and RNA-seq sequence datasets. These datasets provide the molecular foundation for studying gene expression and evolutionary patterns. However, there are no reports on the proteomic data of A. hypogaea cv. Tifrunner, which limits understanding of its gene function and protein level ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In the leaf, homeologs enriched biosynthetic and metabolic process in At subgenome, while iron ion homeostasis process in Bt subgenome. In the root, homeologs enriched inorganic biosynthesis and metabolism process in At subgenome, while organic biosynthesis and metabolism process in Bt subgenome (Duan et al ., 2022 ). Nevertheless, peanut genome complexity combines allotetraploidy with other gene duplication mechanisms.…”
Section: Differential Expression Between Homeologous Genesmentioning
confidence: 99%
“…In the leaf, homeologs enriched biosynthetic and metabolic process in At subgenome, while iron ion homeostasis process in Bt subgenome. In the root, homeologs enriched inorganic biosynthesis and metabolism process in At subgenome, while organic biosynthesis and metabolism process in Bt subgenome (Duan et al ., 2022 ). Nevertheless, peanut genome complexity combines allotetraploidy with other gene duplication mechanisms.…”
Section: Differential Expression Between Homeologous Genesmentioning
confidence: 99%
“…In maize seedlings, substantial differences in post-transcriptional and translational changes between salt-treated embryo and endosperm were noticed using SWATH-MS, which indicated that the elevation of ABA level was an endosperm-dependent process [ 34 ]. In peanuts, differentially abundant proteins were identified using LC-MS coupled with tandem mass tag (TMT), and it was found that homologous proteins enriched different biological processes between the two subgenomes A and B [ 35 ]. SWATH-MS represents a valuable tool for quantitative proteomics based on its ability to generate reproducible data with the added benefit of allowing reinterrogation of data to improve analytical performance.…”
Section: Proteomic Technology Adopted By Plant Sciencesmentioning
confidence: 99%